High-heat-resistant flame-retardant ABS plastic raw material and preparation method thereof
By adding volcanic stone powder and heat-resistant modifiers to the ABS material and applying a pulsed magnetic field during the preparation process, the problem of insufficient heat resistance and flame retardant performance of ABS material in high temperature environments is solved, efficient modification of the material is achieved, and its comprehensive performance is improved.
Patent Information
- Application Number
- CN202510055237.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing ABS materials have insufficient heat resistance and flame retardant properties in high temperature environments, resulting in a decrease in mechanical properties and deterioration of dimensional stability. It is difficult for traditional preparation processes to achieve uniform dispersion of various additives, which limits the improvement of the overall performance of the material.
By adding volcanic stone powder and heat-resistant modifier to the ABS formula and applying a pulsed magnetic field when adding lubricant, an efficient refining and granulation process is adopted to achieve uniform dispersion and synergistic effects of each component.
It significantly improves the thermal deformation temperature and heat resistance of ABS materials, while enhancing its flame retardant performance and maintaining good comprehensive performance.
Smart Images

Figure BDA0005241216760000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ABS modification, in particular to a high heat-resistant and flame-retardant ABS plastic raw material and a preparation method thereof. Background Art
[0002] In modern industry and daily life, acrylonitrile-butadiene-styrene copolymer (ABS), as a thermoplastic engineering plastic with excellent comprehensive performance, is widely used in many fields such as automobile manufacturing, electronic appliances, and building materials. It has good mechanical strength, dimensional stability, and processing performance, and can meet the basic needs of a variety of products.
[0003] However, with the continuous advancement of technology in various industries, the performance requirements for ABS materials are becoming increasingly stringent. In many application scenarios under high temperature environments, such as peripheral parts of automobile engines, internal structural parts of electronic and electrical equipment, etc., the heat resistance of ordinary ABS can no longer meet the needs. When the temperature rises, the movement of its molecular chain segments intensifies, resulting in a significant decrease in the mechanical properties of the material, poor dimensional stability, and even deformation, softening and other problems, which seriously affect the normal use and service life of the product.
[0004] At the same time, the improvement of fire safety awareness has made the requirements for flame retardant properties of materials more stringent. In electronic and electrical products, once a fire occurs, if the ABS material used inside is not flame retardant enough, it is very easy to promote the spread of fire and cause serious loss of life and property. In the interior decoration materials in the construction field, the materials are also required to have good flame retardant properties to ensure the safety of personnel.
[0005] Existing methods for improving the heat resistance and flame retardancy of ABS, such as simply increasing the amount of flame retardants or heat-resistant additives, can improve the performance to a certain extent, but often lead to deterioration of other properties of the material. In addition, the traditional preparation process is difficult to achieve uniform dispersion of each additive in the ABS matrix, and the synergistic effect of each component cannot be fully exerted, which in turn limits the improvement of the comprehensive performance of the material. Therefore, the development of an ABS plastic raw material with high heat resistance and high flame retardancy and maintaining good comprehensive performance and its efficient preparation method has become an important issue that needs to be solved in the current material field. Summary of the invention
[0006] The object of the present invention is to provide a high heat-resistant and flame-retardant ABS plastic raw material and a preparation method thereof to solve the problems raised in the above background technology.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a highly heat-resistant and flame-retardant ABS plastic raw material comprises the following steps:
[0009] S1. Ingredients
[0010] Select according to weight percentage: brominated epoxy resin 12-18wt%, volcanic stone powder 5-8wt%, heat-resistant modifier 3-5wt%, flame retardant 2-3wt%, lubricant 0.3-0.5wt%, and the balance is ABS resin;
[0011] S2, initial mixing
[0012] Add ABS resin into a high-speed mixer, start stirring, set the speed to 500-800 rpm, add the weighed heat-resistant modifier, brominated epoxy resin, flame retardant, volcanic stone powder and lubricant in sequence, and continue stirring for 10-15 minutes to make the components preliminarily mixed;
[0013] S3, secret refining
[0014] The materials after initial mixing are transferred to an internal mixer, the internal mixing temperature is set to 160-180°C, the rotor speed is 40-60 rpm, and the internal mixing time is controlled to be 15-20 minutes;
[0015] S4, Granulation
[0016] The mixed material is conveyed to a twin-screw extruder, and the screw speed is controlled at 300-400 rpm. After the material is fully melted and plasticized in the extruder, it is extruded into strips through a die head; the extruded strips are cooled and shaped in a water tank, and then cut into uniform particles by a pelletizer to obtain high heat-resistant and flame-retardant ABS plastic raw material particles.
[0017] As an improved solution of the present invention: the ABS resin is selected from medium-high impact ABS, and the ratio of acrylonitrile, butadiene and styrene is 1:1:2. The ABS resin has good comprehensive properties and provides a basis for subsequent modification.
[0018] As an improved solution of the present invention: the particle size of the volcanic rock powder is between 100 and 300 meshes.
[0019] Volcanic rock has good thermal stability and can maintain stable structure and performance at high temperatures. Adding it to ABS can be used as a heat-resistant filler to absorb and disperse heat, reduce the impact of heat on the ABS molecular chain, and thus improve the heat resistance of ABS. At the same time, volcanic rock can form a barrier layer in the ABS matrix, hinder heat transfer, delay the thermal movement and thermal degradation process of the ABS molecular chain, so that ABS can maintain good mechanical properties and dimensional stability at high temperatures, and improve its heat deformation resistance. In addition, volcanic rock will affect the crystallization process of ABS, promote the crystallization of ABS molecular chains, and increase crystallinity. The increase in crystallinity can enhance the heat resistance of ABS, because the molecular chains in the crystallization area are more regularly arranged, the intermolecular forces are stronger, and higher temperatures are required to soften and deform them.
[0020] Brominated epoxy resin is a highly efficient brominated flame retardant with good compatibility with ABS. It can capture free radicals in the gas phase, inhibit combustion reactions, and provide excellent flame retardant effects.
[0021] As an improved solution of the present invention: the heat-resistant modifier includes 75% to 85% by mass of maleic anhydride, 10% to 22% by mass of polysiloxane and 3% to 5% by mass of glutarimide.
[0022] Maleic anhydride: It can increase the heat resistance of ABS. It can reduce the interfacial tension, improve the compatibility and adhesion between phases, and enhance the interaction between ABS molecular chains, thereby limiting the thermal movement of molecular chains and improving the heat resistance of ABS.
[0023] Polysiloxane: It can increase the heat resistance of ABS. The Si-O bond in the molecular structure of polysiloxane has the characteristics of high bond energy, large molecular volume, and low cohesive energy density, so it has good high temperature resistance, hydrophobicity, weather resistance and air permeability. Adding polysiloxane to ABS can form a barrier layer between ABS molecular chains, hinder the transfer of heat, and reduce the impact of heat on ABS molecular chains.
[0024] Glutarimide: The molecule contains imide groups, which have high polarity and rigidity. When it is added to ABS resin, it will produce strong interactions with the polar groups on the ABS molecular chain, such as hydrogen bonds, van der Waals forces, etc. These interactions can limit the movement of the ABS molecular chain, making the molecular chain more regularly arranged, thereby improving the heat resistance of the material. At the same time, glutarimide itself has good thermal stability and is not easy to decompose or react chemically at high temperatures. When it is evenly dispersed in ABS resin, it can absorb and transfer heat to a certain extent, reduce the damage of heat to the ABS molecular chain, and thus improve the heat deformation temperature and heat resistance of the ABS material.
[0025] As an improved solution of the present invention: the preparation method of the heat-resistant modifier is: in a reaction kettle, maleic anhydride is heated to 120-130°C to melt it, polysiloxane is slowly added under stirring, and stirring is continued for 30-40 minutes, and the stirring speed is controlled at 300-500 rpm, followed by adding glutarimide, heating to 150-160°C, and reacting for 1-2 hours to obtain a uniform heat-resistant modifier.
[0026] As an improved solution of the present invention: the flame retardant is antimony trioxide, and the lubricant is zinc stearate.
[0027] As an improved solution of the present invention: in step S2, a pulsed magnetic field is applied to the mixed material when the lubricant is finally added, and the application time of the pulsed magnetic field is from 1 to 2 minutes before the addition of the lubricant to 1 to 2 minutes after the addition of the lubricant, and the lubricant is added 4 to 6 times in total.
[0028] As an improved solution of the present invention: the frequency of the pulsed magnetic field is 40-50 Hz, and the period is 0.02-0.025 s.
[0029] As an improved solution of the present invention: in step S4, the temperature of each section of the twin-screw extruder is set as follows:
[0030] The first stage: 180-190℃;
[0031] The second stage: 190-200℃;
[0032] The third stage: 200-210℃;
[0033] The fourth stage: 210-220℃;
[0034] The fifth stage: 220-230℃;
[0035] Machine head: 220-230℃.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The present invention can effectively increase the crystal strength between ABS molecular chains and reduce the damage of heat to ABS molecular chains by adding volcanic lime and heat-resistant modifier to the ABS formula, thereby improving the heat deformation temperature and heat resistance of ABS materials.
[0038] 2. The present invention improves the modification efficiency of the entire ABS raw material by applying a pulsed magnetic field to the mixed material when adding the lubricant, and also further improves the flame retardancy and heat resistance of ABS. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] In an embodiment of the present invention, a highly heat-resistant and flame-retardant ABS plastic raw material is prepared by the following preparation process, including the following steps:
[0042] S1. Ingredients
[0043] Select according to weight percentage: brominated epoxy resin 15wt%, volcanic stone powder 6.5wt%, heat-resistant modifier 4wt%, flame retardant 2.5wt%, lubricant 0.4wt%, and the balance is ABS resin;
[0044] The ABS resin is selected from medium-high impact ABS, and the ratio of acrylonitrile, butadiene and styrene is 1:1:2.
[0045] The particle size of the volcanic rock powder is between 200 meshes, and the heat-resistant modifier includes 80% by mass of maleic anhydride, 16% by mass of polysiloxane and 4% by mass of glutarimide.
[0046] The preparation method of the heat-resistant modifier is as follows: in a reaction kettle, maleic anhydride is heated to 125°C to melt it, polysiloxane is slowly added under stirring, stirring is continued for 35 minutes, the stirring speed is controlled at 400 rpm, glutarimide is then added, the temperature is raised to 155°C, and the reaction is carried out for 1.5 hours to obtain a uniform heat-resistant modifier.
[0047] The flame retardant is antimony trioxide, and the lubricant is zinc stearate.
[0048] S2, initial mixing
[0049] Add ABS resin into a high-speed mixer, start stirring, set the speed to 650 rpm, add the weighed heat-resistant modifier, brominated epoxy resin, flame retardant, volcanic stone powder and lubricant in sequence, and continue stirring for 12.5 minutes to make the components preliminarily mixed;
[0050] When the lubricant is added at the end, a pulse magnetic field is applied to the mixed material, and the application time of the pulse magnetic field starts from 1.5 minutes before the lubricant is added to 1.5 minutes after the lubricant is added, and the lubricant is added 5 times in total. The frequency of the pulse magnetic field is 45 Hz, and the period is 0.022 s.
[0051] S3, secret refining
[0052] The initially mixed materials were transferred to an internal mixer, the internal mixing temperature was set to 170°C, the rotor speed was 50 rpm, and the internal mixing time was controlled at 17.5 minutes;
[0053] S4, Granulation
[0054] The mixed material is conveyed to the twin-screw extruder. The temperature of each section of the twin-screw extruder is set as follows:
[0055] The first stage: 185℃;
[0056] Second stage: 195℃;
[0057] The third stage: 205℃;
[0058] Section 4: 215°C;
[0059] Section 5: 225°C;
[0060] Machine head: 225℃;
[0061] The screw speed is controlled at 350 rpm. After the material is fully melted and plasticized in the extruder, it is extruded into strips through the die head. The extruded strips are cooled and shaped in a water tank, and then cut into uniform particles by a pelletizer to obtain high heat-resistant and flame-retardant ABS plastic raw material particles.
[0062] Example 2
[0063] The difference between this embodiment and embodiment 1 is that in step S1, the following are selected according to weight percentage: 12 wt% of brominated epoxy resin, 5 wt% of volcanic rock powder, 3 wt% of heat-resistant modifier, 2 wt% of flame retardant, 0.3 wt% of lubricant, and the remainder is ABS resin.
[0064] Example 3
[0065] The difference between this embodiment and embodiment 1 is that in step S1, the following are selected according to weight percentage: 18wt% of brominated epoxy resin, 8wt% of volcanic rock powder, 5wt% of heat-resistant modifier, 3wt% of flame retardant, 0.5wt% of lubricant, and the remainder is ABS resin.
[0066] Example 4
[0067] The difference between this embodiment and embodiment 1 is that in step S1, the heat-resistant modifier includes 75% by mass of maleic anhydride, 22% by mass of polysiloxane, and 3% by mass of glutarimide.
[0068] Example 5
[0069] The difference between this embodiment and the embodiment 1 is that in the step S1, the heat-resistant modifier includes 85% by mass of maleic anhydride, 10% by mass of polysiloxane, and 5% by mass of glutarimide.
[0070] Example 6
[0071] The present embodiment is different from the embodiment 1 in that, in the step S2, a pulse magnetic field is applied to the mixed material when the lubricant is finally added, and the application time of the pulse magnetic field starts from 1 minute before the lubricant is added to 1 minute after the lubricant is added.
[0072] Example 7
[0073] The difference between this embodiment and embodiment 1 is that, in step S2, a pulse magnetic field is applied to the mixed material when the lubricant is finally added, and the application time of the pulse magnetic field starts from 2 minutes before the lubricant is added to 2 minutes after the lubricant is added.
[0074] Example 8
[0075] The difference between this embodiment and embodiment 1 is that, in step S2, the frequency of the pulsed magnetic field is 40 Hz and the period is 0.025 s.
[0076] Example 9
[0077] The difference between this embodiment and embodiment 1 is that, in step S2, the frequency of the pulsed magnetic field is 50 Hz and the period is 0.02 s.
[0078] Comparative Example 1
[0079] The difference between this embodiment and embodiment 1 is that in step S1, the batching components do not contain volcanic rock powder.
[0080] Comparative Example 2
[0081] The difference between this embodiment and embodiment 1 is that in step S1, the batching components do not contain a heat-resistant modifier.
[0082] Comparative Example 3
[0083] The present embodiment is different from the embodiment 1 in that, in the step S2, no pulse magnetic field is applied to the mixed material each time the lubricant is added.
[0084] The standard sample bars of the high heat-resistant and flame-retardant ABS plastic raw material prepared above, which were injection-molded and had dimensions of 120 mm in length×10 mm in width×4 mm in thickness, were used for heat resistance and flame retardancy experimental tests.
[0085] The model of the heat deformation temperature tester is XHR-300M, and the model of the horizontal and vertical combustion tester is CZF-3.
[0086] The heat resistance test uses heat deformation temperature (HDT) test, the specific operation is as follows:
[0087] Preparation: Inject an appropriate amount of silicone oil into the heating bath of the heat deformation temperature tester, turn on the heating device, and set the heating rate to 120℃ / h. Install two micrometers on the test stand and adjust their positions so that the gauge heads are in good contact with the upper surface of the sample and the pointers are at the appropriate position of the range.
[0088] Spline installation and loading: Take 3 standard splines and measure their width and thickness to an accuracy of 0.01mm. Place the splines on the support of the test frame so that the length direction of the splines is perpendicular to the support and the center of the splines is located between the two supports. Place a loading pressure head on the upper surface of the splines and apply a bending stress of 1.82MPa through a weight.
[0089] Test process: When the temperature of the heating bath reaches 40℃, start the recorder and begin to record the temperature and dial gauge reading. As the temperature rises, closely observe the changes in the dial gauge pointer. When the deformation of the midpoint of the spline reaches 0.21mm, record the temperature at this time, which is the thermal deformation temperature of the spline.
[0090] The flame retardancy test adopts the UL94 vertical burning test, and the specific operation is as follows:
[0091] Preparation: Connect the horizontal and vertical combustion test machine to the power supply, turn on the equipment switch, and preheat for 10 minutes to allow the equipment to reach a stable working state. Prepare auxiliary materials such as a stopwatch and absorbent cotton.
[0092] Specimen installation: Take 5 standard specimens and use a caliper to measure the length, width and thickness of each specimen to an accuracy of 0.01mm. Fix the specimen vertically on the combustion test stand, ensuring that the lower end of the specimen is about 10mm away from the top of the flame of the alcohol burner.
[0093] Test process: Light the alcohol burner and adjust the flame height to 20mm±2mm. Start the stopwatch and apply the flame to the lower end of the spline at the same time. Keep it for 10 seconds and then remove the flame. Record the flame burning time t1 of the spline after the flame is removed. If the spline goes out within 30 seconds after the flame is removed, apply the flame to the lower end of the spline again for 10 seconds, then remove the flame, and record the second flame burning time t2 and the flameless burning time t3. Observe whether there are drips during the burning process of the spline. If there are drips, observe whether they ignite the absorbent cotton.
[0094] Result evaluation: According to the UL94 standard, the test results of the 5 specimens are comprehensively evaluated. If one of the 5 specimens in each group does not meet the corresponding grade requirements, a group of 5 specimens must be retested. If there are still specimens that do not meet the requirements in the second test, it is determined that the material cannot meet the corresponding flame retardant grade.
[0095] The ABS raw materials obtained by the preparation methods of the above-mentioned Examples 1-9 and Comparative Examples 1-3 were subjected to heat resistance and flame retardancy tests, and the results were obtained as shown in Table 1.
[0096] Table 1
[0097]
[0098] Conclusion 1: Taking Examples 1-3 as experimental comparison, it can be concluded that different ratios in the raw materials will have a certain impact on the heat resistance of the prepared ABS raw materials, and through comparison, it can be seen that the heat resistance effect of Example 1 is the best.
[0099] Conclusion 2: By comparing Example 1 and Examples 4-5, it can be concluded that different ratios of heat-resistant modifiers will have a certain impact on the heat resistance of the prepared ABS raw materials, and by comparison, it can be seen that Example 1 has the best heat resistance effect.
[0100] Conclusion 3: By comparing Example 1 and Examples 6-7, it can be concluded that different application times of the pulsed magnetic field will have a certain impact on the heat resistance of the obtained ABS raw material. If the application time is too long or too short, the heat resistance of the obtained ABS raw material is effectively reduced compared with Example 1. By comparison, it can be seen that the heat resistance effect of Example 1 is the best.
[0101] Conclusion 4: By comparing Example 1 and Examples 8-9, it can be concluded that different parameters of the pulsed magnetic field will have a certain impact on the heat resistance of the obtained ABS raw material, and through comparison, it can be concluded that the heat resistance effect of Example 1 is the best.
[0102] Conclusion 5: Taking Example 1 and Control Examples 1-2 as experimental comparisons, it can be concluded that in the absence of volcanic lime and heat-resistant modifier components, the heat resistance and flame retardancy of the prepared ABS raw material are lower than those of Example 1, indicating that the added heat-resistant modifier and volcanic stone powder effectively improve the heat resistance and flame retardancy of ABS.
[0103] Conclusion 6: Taking Example 1 and Control Example 3 as experimental comparisons, it can be concluded that in the absence of the key process of applying a pulsed magnetic field, the heat resistance and flame retardancy of the prepared ABS raw material are reduced, indicating that applying a pulsed magnetic field when adding a lubricant can effectively improve the heat resistance and flame retardancy of ABS.
[0104] Analysis of the influence of pulse magnetic field key common processes on heat resistance and flame retardancy during ABS modification:
[0105] Heat resistance
[0106] Molecular chain arrangement and movement restriction: During the application of pulsed magnetic field, the effect of magnetic field will make the distribution of ABS resin molecular chains and various added modifiers (such as heat-resistant modifiers, volcanic stone powder) more orderly. The electromagnetic force generated by the pulsed magnetic field can cause the molecular chains to be oriented to a certain extent in the direction of the magnetic field. For maleic anhydride, polysiloxane and glutarimide in the heat-resistant modifiers, the pulsed magnetic field will enhance the interaction between them and the ABS molecular chains. For example, maleic anhydride can react with active sites such as double bonds on the ABS molecular chain, and the pulsed magnetic field will promote this reaction more fully, so that a more stable cross-linked structure is formed between the molecular chains. This cross-linked structure can limit the movement of the molecular chain when heated, thereby improving the heat resistance of the material.
[0107] Energy transfer and absorption: The pulsed magnetic field will change the energy state inside the material during its action. Its parameters such as frequency and period will affect the movement of microscopic particles (such as electrons, ions, etc.) inside the material. When the material is heated, these microscopic particles can absorb and transfer heat. Under the action of the pulsed magnetic field, a state that is more conducive to heat dispersion is formed inside the material. For example, in a system containing volcanic stone powder, the pulsed magnetic field will promote the volcanic stone powder to be better dispersed in the ABS matrix and enhance the interfacial bonding force between it and the matrix. Volcanic stone powder itself has a certain thermal stability and can absorb and disperse heat. The action of the pulsed magnetic field makes the effect of heat absorption and dispersion more significant, thereby increasing the thermal deformation temperature of the material.
[0108] Flame retardancy
[0109] Enhanced dispersion of flame retardants and synergistic effects: Pulsed magnetic fields can improve the dispersion of flame retardants (such as brominated epoxy resin and antimony trioxide) in ABS matrix. Under the action of the magnetic field, the flame retardant particles will overcome the tendency to agglomerate and be more evenly distributed in the material. This allows the flame retardant to play its role more effectively during the combustion process. Brominated epoxy resin can release bromine radicals when burning, and these free radicals can capture active free radicals in the combustion process, thereby inhibiting the combustion reaction. Antimony trioxide, as a synergistic flame retardant, can react with bromine free radicals to enhance the flame retardant effect. The pulsed magnetic field enables them to work better together, and when the material is attacked by flames, it can form a flame retardant barrier in the gas phase more quickly to prevent the spread of flames.
[0110] Carbon layer formation and stability improvement: During the combustion process, the pulsed magnetic field will affect the formation of a carbon layer on the surface of the material. A good carbon layer can isolate oxygen and heat, and is one of the key factors in the flame retardancy of the material. The pulsed magnetic field will cause some components on the surface of the material (such as heat-resistant modifiers and some resin components) to react when heated, forming a denser and more stable carbon layer. For example, polysiloxane will migrate to the surface of the material during the combustion process. Under the action of the pulsed magnetic field, its migration process will be more orderly, and together with other components, it will form a more effective carbon layer, thereby improving the flame retardancy of the material.
[0111] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0112] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a highly heat-resistant and flame-retardant ABS plastic raw material, characterized in that: The steps include: S1. Ingredients Select according to weight percentage: brominated epoxy resin 12-18wt%, volcanic stone powder 5-8wt%, heat-resistant modifier 3-5wt%, flame retardant 2-3wt%, lubricant 0.3-0.5wt%, and the balance is ABS resin; S2, initial mixing Add ABS resin into a high-speed mixer, start stirring, set the speed to 500-800 rpm, add the weighed heat-resistant modifier, brominated epoxy resin, flame retardant, volcanic stone powder and lubricant in sequence, and continue stirring for 10-15 minutes to make the components preliminarily mixed; S3, secret refining The materials after initial mixing are transferred to an internal mixer, the internal mixing temperature is set to 160-180°C, the rotor speed is 40-60 rpm, and the internal mixing time is controlled to 15-20 minutes; S4, Granulation The mixed material is conveyed to a twin-screw extruder, and the screw speed is controlled at 300-400 rpm. After the material is fully melted and plasticized in the extruder, it is extruded into strips through a die head; the extruded strips are cooled and shaped in a water tank, and then cut into uniform particles by a pelletizer to obtain high heat-resistant and flame-retardant ABS plastic raw material particles.
2. The method for preparing a highly heat-resistant and flame-retardant ABS plastic raw material according to claim 1, characterized in that: The ABS resin is selected from medium-high impact ABS, and the ratio of acrylonitrile, butadiene and styrene is 1:1:
2.
3. The method for preparing a highly heat-resistant and flame-retardant ABS plastic raw material according to claim 1, characterized in that: The particle size of the volcanic rock powder is between 100 and 300 meshes.
4. The method for preparing a highly heat-resistant and flame-retardant ABS plastic raw material according to claim 1, characterized in that: The heat-resistant modifier comprises 75% to 85% by mass of maleic anhydride, 10% to 22% by mass of polysiloxane and 3% to 5% by mass of glutarimide.
5. The method for preparing a highly heat-resistant and flame-retardant ABS plastic raw material according to claim 1, characterized in that: The preparation method of the heat-resistant modifier is as follows: in a reaction kettle, maleic anhydride is heated to 120-130° C. to melt it, polysiloxane is slowly added under stirring, stirring is continued for 30-40 minutes, the stirring speed is controlled at 300-500 rpm, glutarimide is then added, the temperature is raised to 150-160° C., and the reaction is performed for 1-2 hours to obtain a uniform heat-resistant modifier.
6. The method for preparing a highly heat-resistant and flame-retardant ABS plastic raw material according to claim 1, characterized in that: The flame retardant is antimony trioxide, and the lubricant is zinc stearate.
7. The method for preparing a highly heat-resistant and flame-retardant ABS plastic raw material according to claim 1, characterized in that: In step S2, a pulse magnetic field is applied to the mixed material when the lubricant is finally added, and the pulse magnetic field is applied from 1 to 2 minutes before the lubricant is added to 1 to 2 minutes after the lubricant is added, and the lubricant is added 4 to 6 times in total.
8. The method for preparing a highly heat-resistant and flame-retardant ABS plastic raw material according to claim 7, characterized in that: The frequency of the pulsed magnetic field is 40-50 Hz, and the period is 0.02-0.025 s.
9. The method for preparing a highly heat-resistant and flame-retardant ABS plastic raw material according to claim 1, characterized in that: In step S4, the temperature of each section of the twin-screw extruder is set as follows: The first stage: 180-190℃; The second stage: 190-200℃; The third stage: 200-210℃; The fourth stage: 210-220℃; The fifth stage: 220-230℃; Machine head: 220-230℃.
10. A high heat-resistant and flame-retardant ABS plastic raw material, prepared by the preparation method of the high heat-resistant and flame-retardant ABS plastic raw material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Ultrahigh heat-resistant and flame-retardant ABS (acrylonitrile butadiene styrene) composition and preparation method thereof
CN102391608A
High-temperature-resistant flame-retardant foamed polypropylene master batch and preparation method thereof
CN115232401A
Preparation process of high-strength wear-resistant copper alloy transmission worm gear for rock drill
CN115365774A
Flame retardant composition, flame retarded resin composition and method for flame retardation
JP2001131553A
Insulation spray foam composition comprising glass wool
KR102532293B1